Ticking Boxes or Making a Difference? The Real Impact of Monitoring Community Projects of Poverty Alleviation - DIPELA, PERCY (Community Development Journal, 2025)
Monitoring and evaluation (M&E) are central to community development projects, typically couched as necessary for accountability, learning, and measuring impact. There is a widespread suspicion that monitoring too often benefits bureaucracy more than meaningful social change. This article considers the tension between compliance-oriented monitoring and transformative effects. Based on critical literature and empirical data, it asks whether existing M&E practice can be disproportionately donor-focused and data-driven at the expense of community empowerment and learning. It contends that monitoring is necessary, but its worth depends on its design and implementation. The article invites a move towards participatory, context-sensitive monitoring practice focused on local relevance, learning, and long-term effects rather than box-ticking rituals.